Organizational "emotion work" through consciousness-raising: An analysis of a feminist organization - Reger, Jo (Qualitative Sociology, 2004)
In this article I explore how organizational processes link to certain emotional responses, as a way of investigating more fully the role emotions play in social movements. Through the construction of a case study of a feminist group, the New York City chapter of the National Organization for Women (NYC NOW), I analyze how certain emotions, such as anger, alienation, hopelessness and frustration, are redefined within an organizational context. I find that consciousness-raising serves as the organizational process that helps transform personal emotions into a collectively defined sense of injustice. This transformation has the potential of creating actors dedicated to chapter activism.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; care; discipline; militance; mouvements féministes; new york; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; états-unis; étude qualitative